Peran Media Massa terhadap Perilaku Ibu dalam Upaya Pencegahan Demam Berdarah pada Rumah Tangga di Kota Yogyakarta - Asniati Djaswadi Dasuki, Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: The incidence of dengue hemorrhagic fever (DHF) is increasing dramatically especially in tropical areas. DHF can cause death. It is predicted that 25 thousand people die every year because of DHF. Control of DHF through fogging and use of abate can reduce population of Aedes aegypti mosquitos but it is costly and use in improper dosage can cause resistance to insecticide. The best way to prevent the disease is eradicating vector larvae through 3 activities (draining, burying and covering). Such efforts can be done by mothers in their household. Meanwhile in doing these efforts mothers may be influenced by some factors, i.e. mass media, knowledge and attitude of mothers about DHF.Objective: The objective of the study was to identify factors related to mothers’ behavior in preventing hemorrhagic fever in the household.Method: This was an observational study with cross sectional design. The sample of the study was as many as 100 mothers. Data were collected through questionnaires and analyzed using univariate, bivariate and multivariate techniques.Result: Variable of role of mass media was statistically significant as predictor of DHF prevention behavior (p<0.05) with moderate relationship level (r=0.352). Variables of knowledge and attitude were statistically significant with p<0.05 but they had negative relationship.Conclusion: Mass media can significantly affect mothers’ behavior in preventing DHF in the household.Keywords: mass media, knowledge, attitude, DHF, prevention